Intrathecal application of the antimicrobial peptide CRAMP reduced mortality and neuroinflammation in an experimental model of pneumococcal meningitis. Issue 2 (August 2015) - Dörr, Arndt; Kress, Eugenia; Podschun, Rainer; Pufe, Thomas; Tauber, Simone C.; Brandenburg, Lars-Ove
Summary Antimicrobial peptides (AP) are important components of the innate immune system. Our previous work revealed a higher mortality rate and up-regulation of proinflammatory gene expression as well as glial cell activation in cathelicidin-related antimicrobial peptide (CRAMP)-deficient mice after bacterial meningitis. However, the influence of CRAMP application on the progression of inflammation and its impact on mortality after bacterial meningitis remains unknown. To assess the effects of continuous CRAMP exposure in the brain, C57BL/6 wildtype mice were given intracerebroventricular infusion of CRAMP to investigate the effects on mortality, glial cell activation and inflammation in a mouse model of pneumococcal meningitis using immunohistochemistry and realtime RT-PCR. Our results revealed a decrease of mortality after CRAMP infusion. The intrathecal CRAMP infusion after pneumococcal meningitis resulted in a decreased mRNA expression of pro-inflammatory cytokines, whereas the immune responses including the expression of pattern recognition receptors and chemokines were increased in bacterial meningitis. Taken together, the results support the important role of CRAMP as part of the innate immune response against pathogens in bacterial CNS infections. The APs may be a promising approach for the development of an adjuvant therapy for bacterial meningitis.